Last updated at Dec. 8, 2016 by Teachoo

Transcript

Misc 5 Show that if A ⊂ B, then C – B ⊂ C – A. Introduction A = {1, 2} B = {1, 2, 3} C = {1, 2, 3, 4} C – B = {1, 2, 3, 4} – {1, 2, 3} = {4} C – A = {1, 2, 3, 4} – {1, 2} = {3, 4} {4} ⊂ {3,4} So, C – B ⊂ C – A Misc 5 Show that if A ⊂ B, then C – B ⊂ C – A. To show: If A ⊂ B, then C – B ⊂ C – A Proof: Let x be in an element of set C – B i.e. x ∈ C – B ⇒ So, x is in set C, but not in set B , i.e. x ∈ C and x ∉ B ⇒ x is in set C, but not in set A i.e. x ∈ C and x ∉ A ⇒ So, x is in set C – A i.e. x ∈ C – A ∴ If x ∈ C – B ,then x ∈ C – A i.e. If an element belongs to the set C – B , it also belongs to the set C – A ⇒ C – B ⊂ C – A Hence proved

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 9 years. He provides courses for Maths and Science at Teachoo.